Optimization of polyphenols extraction from cocoa bean shell using factorial design. (Journal of Bio-Science, 2019)
This investigation aims to establish the optimum parameters to extract polyphenols from cocoa bean shell (CBS). Time, solvent and method of extraction were considered as factors and Total Content of Polyphenols (TCP) expressed as Gallic Acid Equivalent (GAE) was selected as the response. Results showed that using factorial design the optimum conditions were water in reflux during 5 minutes (262.76 ± 20.66 mg GAE/ 100 g). This revealed that CBS represent a high potential of use in food industry, principally in the field of functional food development.J. bio-sci. 26: 49-54, 2018